Perbandingan Pendekatan Politik - Ekonomi Media dan Studi Kebudayaan dalam Kajian Komunikasi Massa - Fahrizal Sukma; Udi Rosadi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
he influence of mass media on social and cultural interactions is a growing phenomenon. To come up with ideas that provide a thorough understanding of these events in these circumstances may be difficult for scholars who study the mass media. The political economy of media and cultural studies are two categories of critical approaches that share features, strengths, and weaknesses. By paying sufficient attention to these details, the two techniques can complement and learn from each other. This research seeks to study someone's opinion, response, or perception, so the discussion must be qualitative in nature or use descriptive language, so the writer uses a descriptive research methodology. When analyzing texts and explaining various subject positions or views, mass media studies must adopt a multi-perspective approach, or apply a critical methodology. Keywords: mass media, social and cultural interaction, mass communication